Growth and nutrition in children with ataxia telangiectasia. Issue 12 (29th August 2016) - Stewart, Emma; Prayle, Andrew P; Tooke, Alison; Pasalodos, Sara; Suri, Mohnish; Bush, Andy; Bhatt, Jayesh M
Abstract : Background: Ataxia telangiectasia (A-T) is a rare multisystem disease with high early mortality from lung disease and cancer. Nutritional failure adversely impacts outcomes in many respiratory diseases. Several factors influence nutrition in children with A-T. We hypothesised that children with A-T have progressive growth failure and that early gastrostomy tube feeding (percutaneous endoscopic gastrostomy, PEG) is a favourable management option with good nutritional outcomes. Methods: Data were collected prospectively on weight, height and body mass index (BMI) at the national paediatric A-T clinic. Adequacy and safety of oral intake was assessed. Nutritional advice was given at each multidisciplinary review. Results: 101 children (51 girls) had 222 measurements (32 once, 32 twice, 24 thrice) between 2009 and 2016. Median (IQR) age was 9.3 (6.4 to 13.1) years. Mean (SD) weight, height and BMI Z-scores were respectively −1 (1.6), −1.2 (1.2) and −0.4 (1.4). 35/101 children had weight Z-scores below −2 on at least one occasion. Weight, height and BMI Z-scores declined over time. Decline was most obvious after 8 years of age. 14/101 (14%) children had a PEG, with longitudinal data available for 12. In a nested case control study, there was a trend for improvement in weight in those with a PEG (p=0.10). Conclusions: Patients with A-T decline in growth over time. There is an urgent need for new strategies, including an understanding of why growth falters. We suggest early proactive consideration of PEG from age 8 years onwards to prevent progressive growth failure.